PSR J2150+3427: A Possible Double Neutron Star System - Q. D. Wu; N. Wang; J. P. Yuan; D. Li; P. Wang; M. Y. Xue; W. W. Zhu; C. C. Miao; W. M. Yan; J. B. Wang; J. M. Yao; S. Q. Wang; et al. (The Astrophysical Journal Letters)
PSR J2150+3427 is a 0.654 s pulsar discovered by the Commensal Radio Astronomy FAST Survey. From the follow-up observations, we find that the pulsar is in a highly eccentric orbit ( e = 0.601) with an orbital period of 10.592 days and a projected semimajor axis of 25.488 lt-s. Using 2.7 yr of timing data, we also measured the rate of periastron advance $\dot{ω }$ = 0.0115(4) deg yr ^−1 . An estimate for the total mass of the system using the $\dot{ω }$ gives M _tot = 2.59(13) M _⊙ , which is consistent with most of the known double neutron star (DNS) systems and one neutron star (NS)–white dwarf (WD) system named B2303+46. Combining $\dot{ω }$ with the mass function of the system gives the masses of M _p < 1.67 and M _c > 0.98 M _⊙ for the pulsar and the companion star, respectively. This constraint, along with the spin period and orbital parameters, suggests that it is possibly a DNS system, and we cannot entirely rule out the possibility of an NS–WD system. Future timing observations will vastly improve the uncertainty in $\dot{ω }$ , and are likely to allow the detection of additional relativistic effects, which can be used to modify the values of M _p and M _c . With a spin-down luminosity of $\dot{E}$ = 5.07(6) × 10 ^29 erg s ^−1 , PSR J2150+3427 is a very low-luminosity pulsar, with only the binary pulsar J2208+4610 having a smaller $\dot{E}$ .